The Complex Nature of Parental Substance Use: Examining Past Year and Prior Use Behaviors as Correlates of Child Maltreatment Frequency. (12th May 2017) - Kepple, Nancy Jo
ABSTRACT: Background: Child maltreatment studies predominantly have operationalized parental substance use as dichotomous variables for any use, any harmful/risky use, or any substance use disorder (SUD). This limits our understanding about how a range of use behaviors may contribute to child maltreatment. Objective: Build upon prior studies by incorporating a multi-faceted approach to operationalizing parental substance use. Methods: Cross-sectional, secondary data analyses were conducted using the National Survey of Child and Adolescent Well-being (NSCAW I). The study used weighted negative binomial regression to examine relationships between annual child maltreatment frequency and different ways of operationalizing substance use among 2, 100 parents. Results: Several, inter-related behaviors (i.e., heavy drinking, illicit drug use, polysubstance use, SUD, and prior SUD < 4 years) appeared to be relevant for understanding differences in child maltreatment frequencies. A gradient effect was detected across five substance use behavior patterns: (1) lowest estimated counts were observed for nonusers, light-to-moderate drinkers, and parents with a prior (but not past year) SUD (ӯ < 7.0), (2) slightly higher estimated count was observed for heavy drinkers and/or illicit drug users (ӯ = 9.3), and (3) highest estimated count was observed for parents with past year SUD (ӯ = 17.6). Conclusions/Importance: SUD is a critical screening criteria for potential child harm. Parents reporting risky substance use behaviors may benefit from prevention or brief intervention services related to both their substance use and parenting behaviors. Administrative systems also could benefit from detailed tracking of substance use behaviors for future program evaluation and development.